2015
DOI: 10.1038/srep14310
|View full text |Cite
|
Sign up to set email alerts
|

A novel microtubule de-stabilizing complementarity-determining region C36L1 peptide displays antitumor activity against melanoma in vitro and in vivo

Abstract: Short peptide sequences from complementarity-determining regions (CDRs) of different immunoglobulins may exert anti-infective, immunomodulatory and antitumor activities regardless of the specificity of the original monoclonal antibody (mAb). In this sense, they resemble early molecules of innate immunity. C36L1 was identified as a bioactive light-chain CDR1 peptide by screening 19 conserved CDR sequences targeting murine B16F10-Nex2 melanoma. The 17-amino acid peptide is readily taken up by melanoma cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 62 publications
1
30
0
1
Order By: Relevance
“…We have previously shown that intraperitoneal injections of the anti-tumour CDR peptide C36L1 significantly decrease pulmonary melanoma metastasis in a syngeneic model (24,25). In addition, bone marrow derived myeloid pro-inflammatory dendritic cells (DCs) displayed equivalent anti-tumour effect when tumor antigen-primed DCs were pre-treated with C36L1 ex vivo and adoptively transferred to mice bearing lung melanoma metastasis (24). These findings suggest that the anti-tumour effects induced by C36L1 in vivo may result from the peptide ability to stimulate the host immune response.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that intraperitoneal injections of the anti-tumour CDR peptide C36L1 significantly decrease pulmonary melanoma metastasis in a syngeneic model (24,25). In addition, bone marrow derived myeloid pro-inflammatory dendritic cells (DCs) displayed equivalent anti-tumour effect when tumor antigen-primed DCs were pre-treated with C36L1 ex vivo and adoptively transferred to mice bearing lung melanoma metastasis (24). These findings suggest that the anti-tumour effects induced by C36L1 in vivo may result from the peptide ability to stimulate the host immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic peptides based on Immunoglobulin-CDR sequences have shown promising antitumour properties, and some of these peptides display immune stimulatory functions (22,(24)(25)(26). The C36 V L CDR1 peptide (C36L1) was initially identified as an anti-melanoma agent (25) that inhibits melanoma cells survival and proliferation (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations